ORGANIZATION OF PROTECTION AND LIFE SUPPORT OF THE POPULATION FOR EMERGENCY SITUATIONS (Multidisciplinary Journal of Science and Technology, 2025)
This article addresses the comprehensive framework for the organization of protection and lifesupport for populations during emergency situations. It examines various strategies andmethods to ensure safety, timely evacuation, provision of basic needs, and medical assistancein times of crisis. Emphasizing preparedness, coordination among agencies, and communityinvolvement, this paper proposes actionable recommendations to enhance emergency responseeffectiveness and resilience.